O desenvolvimento das cinco maiores economias mundiais mais a do Brasil: uma análise comparativa entre indicadores contemporâneos selecionados - (:unkn) unknown (Universidade Federal do Pampa, 2017)
The concept of economic development only got its strength in the twentieth century, but his theoretical and empirical origins was established in the previous period, from the eighteenth century. Throughout history, different concepts of economic development have emerged, enriching their notion and, in this way, different forms emerged for their measurement. From this context, the present study aims to analyze the five largest world economies plus Brazil, considering the GDP at purchasing power parity in 2015, and to verify their performance when measured by different indicators of economic development. By the nature of the study, it is classified as a quantitative method, where the main method used was the comparative one, also making use of auxiliary methods, such as the bibliographic and documentary method, besides the secondary data. Among the various indicators already developed for development measures, for this study were selected some that constitute either as classic measures (GDP and GINI Index) or as an institutional effort to complex the indicator (HDI) or as an attempt to measure one profound modification of the design of development (FIB - Gross Domestic Happiness). To reach the main objective, firstly it was presented the aspects related to the notion of development, presenting the historical perspective of its construction, emphasizing the different concepts considered for the construction and attempt of its understanding. It was also presented the concept of development indicators, classifying its main objectives. To understand the structural changes that have led to the growth of nations, it was necessary to make a historical retrospective of the countries. In this sense, it was possible to observe the visible influence that globalization exerts in the countries and, thus, presented the economies of each country, covering aspects such as the types of policies used, the main products produced, at which moment of the industrialization occurred and the opening of the economy. Aiming to understand if these countries, with a high level of capital, still represent themselves as developed to include other aspects, such as social and environmental, these conditions were analyzed through the methodology proposed by each selected indicator. The results indicate that although the high economic growth of the countries studied, they do not necessarily continue to develop in the other optics. The social problems in these countries link a low outlook on other indicators and the apparent government neglect of certain parts of the population. Thus, for development to take place, it is necessary that the evolution of some beliefs and customs take place, differently in each country.
Keywords: Desenvolvimento; Crescimento; Indicadores; Development; Growth; Indicators; CNPQ::CIENCIAS SOCIAIS APLICADAS